[Ulotka z powstańcem 1863 r.] . Flier with a January Uprising insurgent - Solidarność Małopolska. (Solidarność Małopolska, 1987)
Red and black print on white paper. Flier, issued to commemorate the 1863 January Uprising, contains a graphic image which represents an insurgent carrying a banner. Price: 100 zł.